How academic research and news media cover climate change: a case study from Chile - Cortés, Pablo A.; Quiroga, Riva (Frontiers in Communication, 2023)
Climate change has significant impacts on society, including the environment, economy, and human health. To effectively address this issue, it is crucial for both research and news media coverage to align their efforts and present accurate and comprehensive information to the public. In this study, we use a combination of text-mining and web-scrapping methods, as well as topic-modeling techniques, to examine the similarities, discrepancies, and gaps in the coverage of climate change in academic and general-interest publications in Chile. We analyzed 1261 academic articles published in the Web of Science and Scopus databases, and 5024 news articles from eight Chilean electronic platforms spanning the period from 2012 to 2022. The findings of our investigation highlight three key outcomes. Firstly, the number of articles on climate change has increased substantially over the past decade, reflecting a growing interest and urgency surrounding the issue. Secondly, while both news media and academic research cover similar themes, such as climate change indicators, climate change impacts and mitigation and adaptation strategies, the news media provides a wider variety of themes, including climate change and society and climate politics, which are not as commonly explored in academic research. Thirdly, academic research offers in-depth insights into the ecological consequences of global warming on coastal ecosystems and their inhabitants. In contrast, press media tends to prioritize the tangible and direct impacts, particularly on agriculture and urban health. By integrating academic and media sources in our study, we shed light on their complementary nature, facilitating a more comprehensive communication and understanding of climate change. This analysis serves to bridge the communication gap that commonly exists between scientific research and news media coverage. By incorporating rigorous analysis of scientific research with the wider reach of news media, we enable a more informed and engaged public conversation on climate change.